TEFL Students’ Language Learning Strategies: The Case of One State Islamic Institute in Indonesia - Dairabi Kamil; Suhaimi Suhaimi; Rudi Hartono; Aridem Vintoni (Ta'dib: Jurnal Pendidikan Islam, 2017)
The purpose of this quantitative study was  to examine the language learning strategies of TEFL students at State Islamic Institute of Kerinci. The data were collected through a survey dengan mengunakan the Indonesian version Oxford’s (1990) Strategy Inventory for Language Learning and were analyzed through the Rasch Analysis. The results revealed that metacognitive strategy and social strategy were the most and the least frequently used strategy respectively. Considerable differences existed in the second most frequently used strategy across the variable of gender. For male respondents, it was the compensatory strategy, while for female respondents, it was the affective strategy. In addition, cognitive strategy, the third most frequently used strategy by male respondents, is the last for their female counterparts. The first three most frequently used strategies by male respondents were dominated by the direct type of strategies, while for female respondents these were dominated by the indirect ones.